Creating the productive workplace : places to work creatively - Clements-Croome, Derek (Routledge, Taylor & Francis Group, 2018)
The built environment affects our physical, mental and social well-being. Here renowned professionals from practice and academia explore the evidence from basic research as well as case studies to test this belief. They show that many elements in the built environment contribute to establishing a milieu which helps people to be healthier and have the energy to concentrate while being free to be creative. The health and well-being agenda pervades society in many different ways but we spend much of our lives in buildings, so they have an important role to play within this total picture. This demands us to embrace change and think beyond the conventional wisdom while retaining our respect for it. Creating the Productive Workplace shows how we need to balance the needs of people and the ever-increasing enabling technologies but also to take advantage of the healing powers of Nature and let them be part of environmental design. This book aims to lead to more human-centred ways of designing the built environment with deeper meaning and achieve healthier and more creative, as well as more productive places to work.